A qualitative analysis of postpartum contraceptive choice. (3rd July 2018) - Booth, Kathleen; Sundstrom, Beth; DeMaria, Andrea L.; Dempsey, Angela
ABSTRACT: Background: The World Health Organization recommends a minimum 24-month birth-to-pregnancy interval to improve maternal and child health. Postpartum contraception is a mechanism to achieve optimal birth spacing and prevent unintended pregnancy, which may reduce health disparities and inequalities in health status among new mothers and their children. This study investigated women's communication channel preferences, as well as patient engagement and shared decision making about contraceptive method choice and use in the postpartum period. Method: Researchers conducted six focus groups with 47 women receiving postpartum care at an outpatient clinic. A semi-structured focus group protocol was created and tested. A constant comparative approach provided an inductive method of analysis. HyperRESEARCH 3.5.2 qualitative data analysis software facilitated coding based on the health belief model. Results: Participants included women 18–39 years of age with an average of 1.7 children. The majority of participants utilized Medicaid (53%) and self-identified as Black (49%) or White (43%). Participants discussed interpersonal, mass media, and new media channels featuring messages about contraception, including long-acting reversible contraception (LARC). These women negotiated complex social norms, including preferring the Internet as a primary source of information and avoiding mass media. Participants balanced messages from social networks, including physician counseling and the power of personal experiences of friends and family in contraceptive decision making. Conclusions: This study demonstrated women perceive the voices of lay experts online as the most influential source of information and prefer to receive contraceptive information online and in-person during the prenatal and postpartum period.